Visualisasi Indeks Cuaca Kebakaran di Aek Godang Berbasis Pendekatan Machine Learning - Kerista Tarigan; Edison Kurniawan; Sri Wahyuni (Journal of Computation Physics and Earth Science (JoCPES), 2021)
Forest fires are a major natural issue, making temperate and environmental harm whereas dangering human lives. The examined and study for timberland fire had been worn out Aek Godang, Northern Sumatera, Indonesia. There are 26 hotspots in 2017 near Aek Godang, North Sumatera, Indonesia. In this consider, we utilize an information mining approach to prepare and test the information of woodland fire and Fire Weather Index (FWI) from meteorological information. The point of this ponders to anticipate the burned range and distinguish the woodland fire in Aek Godang ranges, North Sumatera. The result of this considers shown the Fire battling and avoidance movement may be one reason for the watched need of relationship. The reality that this dataset exists demonstrates that there's as of now a few exertions going into fire avoidance.